0
$\begingroup$

Could someone help me to prove this identity: $\sum_\limits{k=0}^n \binom{-\frac{1}{2}}{k}\binom{-\frac{1}{2}}{n-k} = (-1)^n$ without using of the infinite series, please? I don't know how to do this without the Vandermonde's identity for real numbers...

$\endgroup$
  • 1
    $\begingroup$ You asked the same question twice. Weren't you satisfied by robjohn's answer? My proposal is to merge both questions into a single one. $\endgroup$ – Jack D'Aurizio Dec 30 '17 at 10:21
1
$\begingroup$

Vandermonde's identity is $$\binom{a+b}n=\sum_{k=0}^n\binom ak\binom b{n-k}.\tag{1}$$ If $a$ and $b$ are non-negative integers (1) has a combinatorial proof. (Count number of $n$-person committees you can make from a pool of $a$ women and $b$ men). The general case can be deduced from this. The difference between the sides in (1) is a polynomial $f(a,b)$ with degree at most $n$ in $a$ and also at most $n$ in $b$. If $a$ is a nonnegative integer then $f(a,0)=f(a,1)=\cdots=f(a,n)=0$ and as $f$ has degree $\le n$ in $b$ then $f(a,b)=0$ for all nonnegative integers $a$ and all $b$. Now for any $b$, $f(0,b)=f(1,b)=\cdots=f(n,b)$. Likewise this implies that $f(a,b)=0$ for all $a$ and $b$, in particular for $a=b=-\frac12$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.